Preparing for Indonesian Agricultural Transformation in The Society Era 5.0 - Mercy Bientri Yunindanova (Agrosains : Jurnal Penelitian Agronomi, 2022)
Indonesia is an agricultural country with one of its main incomes from the agricultural sector. Indonesia's position in the equatorial region and tropical climate favors Indonesia as a country with megabiodiversity. Indonesia has a variety of regional conditions with agricultural management techniques according to the needs of farmers in the region. Agricultural technology is the key to agricultural transformation, marking changes in each era, including the era of society 5.0. Agriculture in the Society 5.0 era will blend technology with automation, where technology can play a role in replacing and complementing agricultural activities. This set of technologies will allow farmers to control agricultural commodities and their environment. Agricultural activities are carried out using IoT (Internet of Things), AI (Artificial Intelligence), Big Data, and robotic technology. Agriculture in the Society 5.0 era was based on smart agriculture with the concept of precision farming. Indonesia has a great opportunity to be ready to face agriculture in the era of Society 5.0. through 7 TTPS (7 Stages of Transformation of Agriculture Society 5.0) namely Commitment and Policy, Human resources, Research, Data management, Transition, Tools, and Cyber protection. With the right and gradual transformation process, as well as the ability to integrate and synergize across disciplines and across institutions, the transformation process will be able to run well.